Application of Demand-side Technology in Power System Intelligent Regulation - Zhu, Hui; Li, Zhaoming; Chen, Sisi; Peng, Xiaojie (Distributed Generation & Alternative Energy Journal, 2021)
To reduce peak demand for electricity, smooth load curve shape, improve power system safety and efficiency, this paper, by using intelligent home appliance user operation comfort model is set up to quantify the acceptance, this paper proposes a maximum minimum load management algorithm based on optimization strategy to change electric power use time and power con- sumption mode.The results show that the proposed model and algorithm can forecast and manage the power load well, and can reduce the peak to average ratio by 14.3% and the total expenditure by 15.3% while maintaining the operating comfort of power users to the maximum.The load management problem of multiple power users can reach Nash equilibrium in a finite number of iterations, and this Nash equilibrium point is also the global optimal point.